2022
DOI: 10.3389/fnut.2022.851275
|View full text |Cite
|
Sign up to set email alerts
|

A machine-learning approach for predicting the effect of carnitine supplementation on body weight in patients with polycystic ovary syndrome

Abstract: The present study aimed to explore the effect of carnitine supplementation on body weight in patients with polycystic ovary syndrome (PCOS) and predict an appropriate dosage schedule using a machine-learning approach. Data were obtained from literature mining and the rates of body weight change from the initial values were selected as the therapeutic index. The maximal effect (Emax) model was built up as the machine-learning model. A total of 242 patients with PCOS were included for analysis. In the machine-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…When the OFV was increased (>6.63; χ 2 , α=0.01, d.f.=1), significance was achieved in the final model. Our previous studies were mainly based on the methodology used in the present study, and indicated that the present method was reliable and acceptable (32)(33)(34)(35).…”
Section: Effects Of Dapagliflozin On Body Weight In Patients With Typ...mentioning
confidence: 62%
“…When the OFV was increased (>6.63; χ 2 , α=0.01, d.f.=1), significance was achieved in the final model. Our previous studies were mainly based on the methodology used in the present study, and indicated that the present method was reliable and acceptable (32)(33)(34)(35).…”
Section: Effects Of Dapagliflozin On Body Weight In Patients With Typ...mentioning
confidence: 62%